The Ideology of Spiritual Practices in Persatuan Seni Silat Cekak Malaysia (PSSCM) - Nur Enanee Ezani; Nozira Salleh (UIN Sunan Kalijaga Yogyakarta, 2021)
Malay martial arts is often associated with the practice that contains elements of superstitions. This can be seen when religious authorities such as the Department of Islamic Development Malaysia or popularly known as (JAKIM) and Selangor Islamic Religious Department (JAIS) published guideline books for martial arts associations in Malaysia according to Islam. Therefore, there is a martial arts association in Malaysia, namely Persatuan Seni Silat Cekak Malaysia (PSSCM) have a clear vision of upholding the original Malay Silat, especially Malaysian martial arts, and clean from all superstitions which are not align with the Islamic faith. Therefore, the approach of this study is to identify the ideology of spiritual practices found in PSSCM that are free from superstitions and capable of educating morals and noble practices. This study uses a qualitative methodology based on content analysis and this study will analyze documents related to the ideology of spiritual practice in PSSCM. The study found that PSSCM has an ideology of spiritual practices that are aimed at educating the spiritual and the virtuous. This practice also does not conflict with the Islamic Shariᶜa. Therefore, PSSCM is not merely educating people to take care of themselves but also signaling them with good moral characters.